IMPORTANCE OF POTATO POWDER EXTRACTION TECHNOLOGY IN PRODUCTION AND INDUSTRY - Meliboyev, Mirazam; Makhmudova , Gulsanam; Muydinova , Nigora (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract: Objective. Potatoes were originally used as food by South American Indians. Its cultivation began about ten thousand years ago in the territory of Peru. Information about potatoes reached Europe only in the 16th century, and it was widely used in cooking from the 18th century. Currently, potatoes are grown in all regions of the world. It has about 4000 species. Russia, Belarus, Ireland and China are the countries where potatoes are consumed the most. At first, potatoes were used as a houseplant and planted in flower pots to decorate the house. Methods. In our research work, a technological line for drying and juicing potatoes from nodular products in the belt drying chamber of a convective drying device. Introduction. Potato is a vegetable that was imported from the sea and was brought to Europe from South America in the middle of the 17th century. Potatoes contain many types of trace elements, B group and vitamins A, C, U, PP group, potassium, zinc and magnesium, calcium. It contains carbohydrates, iron, phosphorus, and iodine elements. Due to its starch content, it gives energy to the body and is extremely satiating. Potato nodules contain starch (about 20 proteins, sugar) and other substances. Alcohol, starch and glucose are obtained from them. It is known that the demand for dried fruits and vegetables in our country is increasing year by year. That is, the production of high-quality, low-cost products with high food value and innovative energy-saving high sublimation and convective drying technologies are widely used in the food industry today,is being used.